PENGARUH PENERAPAN METODE KARYAWISATA TERHADAP HASIL BELAJAR MENULIS TEKS BERITA KELAS VII SMPN 1 WATANSOPPENG: THE EFFECT OF THE FIELD TRIP METHOD ON THE LEARNING OUTCOMES OF WRITING NEWS TEXT IN CLASS VII SMPN 1 WATANSOPPENG - Hasriani; Sahrani, Nurfitra; Saleh, Muhammad (Journal of Applied Linguistics and Literature, 2024)
The Effect of Applying the Field Trip Method on the Learning Outcomes of Writing News Texts for Class VII Students at SMPN 1 Watansoppeng. This research aims to; (1) Describe the results of learning to write news texts before using the Class VII field trip method at SMPN 1 Watansoppeng; (2) Describe the results of learning to write news texts after using the Class VII field trip method at SMPN 1 Watansoppeng; This research is a quantitative type of research with a Pre-Experimental Design type of design. The research results showed that the student's pretest was 51.27 and the posttest result was 68.96. The normality test of the pretest and posttest data shows that the data is normally distributed. Furthermore, the results of the posttest data homogeneity test show that the data is homogeneous. Based on the results of the paired sample test which shows that it is 8.099 > 1.706, it can be concluded that the field trip method is used in learning to write news texts in Class VII SMPN 1 Watansoppeng